Morphological aspects of multi-nucleated Trichomonas vaginalis from cervical cancer patients in Malaysia - Mat Yusof, Afzan; Kumar, Suresh (2013)
Trichomonas vaginalis, a flagellated protozoan parasite is commonly found in the genitourinary tract. Binary fission is the only plausible mode of reproduction shown thus far but this does not account for the rapid growth rates seen in in vitro cultures within a short period of time. We have previously shown ultrastructural evidence of another asexual mode of reproduction other than binary fission seen in Trichmonas vaginalis. The present study compares the number of multi-nucleated forms isolated from cervical neoplasia (CN) and non-cervical neoplasia (NCN) patients. The present study highlights the detailed characterization of the morphological aspects of 4 CN and 4 NCN isolates by using fixed staining and fluorescent staining of nuclear content. A sequential transformation highlighting nuclear division leading to the formation of multi-nucleated parasite is shown. We observe that this mode of reproduction is not commonly seen and postulate that it could be triggered to increase progeny formation due to stress. These forms were viable when tested with trypan blue dye test. The study confirms that the parasite divides by an asexual mode of reproduction other than binary fission and the parasites isolated from cervical neoplasia showing larger numbers of nuclei accounting for higher parasite numbers in cultures.